Laryngeal Amyloidosis- an Unusual Cause of Hoarseness: a Case Report - Mishra, Sudeep; Shah, S P; Chhetri, S T; Shah, R; Sanjel, A (Journal of BP Koirala Institute of Health Sciences, 2019)
Amyloidosis is a benign condition with abnormal deposition of extracellular protein in various parts of the body. Laryngeal amyloidosis is a rare clinical condition. Hoarseness of voice is one of the most common symptoms presenting to a clinician. The clinical appearance mimics the early laryngeal carcinoma. It remains a diagnostic challenge to the clinician. It is essential to differentiate laryngealamyloidosis from malignancy as most of the findings mimic laryngeal carcinoma. We report a case of laryngeal amyloidosis that presented with hoarseness, to differentiate it from laryngeal malignancy for effective management.